ã€Šæ±‰è¯å£è¯é€Ÿæˆã€‹å£è¯è¯¾æ•™æçš„ç”Ÿè¯åˆ†æž - Pandame, Dian Novianty; Thamrin, Lily; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTeaching materials are like the bridge that connect the teacher and the students. They emphasize â€œteachingâ€ from the teacher and â€œlearningâ€ from the students. In a textbook, the vocabulary has an important role. The vocabulary is the basic material that constructs a textbook which we have to master it if we want to learn a language. To know the writing system of the vocabularies in teaching materialã€Š hanyu kouyu sucheng ã€‹ï¼Œthe writer used literature study method to research the number, the difficulty, and the variety of the vocabularies, such as noun, adjective, and so on. After doing the research, the writer could conclude in general that the writing of teaching materialã€Š hanyu kouyu sucheng ã€‹had been in accordance with scientific principle which had a clear level of vocabulary difficulty, in which every level of the textbook had different difficulty, the higher of the level then the vocabulary in the textbook also became more difficult. After doing this research, the writer hopes that the result of this research can provide reference and suggestion to the Mandarin teacher in closing the textbook or teaching material for teaching a conversation.Keywords: Teaching Material for Conversation, Vocabulary, Hanyu Kouyu Sucheng